Sulfadiazine Plus Pyrimethamine Therapy Reversed Multiple Behavioral and Neurocognitive Changes in Long-Term Chronic Toxoplasmosis by Reducing Brain Cyst Load and Inflammation-Related Alterations - Castaño, Barrios Leda; Silva, Andrea Alice; Hernandez-Velasco, Lina L; Pinheiro, Ana Paula Da Silva; Gibaldi, Daniel; Mineo, José Roberto; Silva, Neide Maria; Lannes-Vieira, Joseli (Frontiers in Immunology, 2022)
Toxoplasma gondii infects one-third of the world population. For decades, it has been considered a silent lifelong infection. However, chronically T. gondii-infected persons may present psychiatric and neurocognitive changes as anxiety, depression, and memory loss. In a model of long-term chronic infection, behavioral alterations parallel neuroinflammation and systemic high cytokine levels, and may reflect brain cyst load. Recent findings support that in chronic infection an active parasite-host interplay involves an immune-mediated control of tissue cysts. Here, we tested the idea that etiological treatment in chronic phase may add advantage to intrinsic immune-mediated cyst control and impact behavioral changes. Thus, we combined sulfadiazine-plus-pyrimethamine (S+P), the first-choice therapy for toxoplasmosis, to study the association of brain cyst load and biological processes related to the immune response (neuroinflammation, blood-brain barrier -BBB- disruption and serum cytokine levels), with behavioral and neurocognitive changes of long-term chronic infection. Female C57BL/6 mice (H-2b) were infected (5 cysts, ME-49 strain) and treated with S+P from 30 to 60 days postinfection (dpi), compared with vehicle (Veh)-treated and noninfected controls. At endpoints (pre-therapy, 30 dpi; S+P therapy, 60 dpi; after ceased therapy, 90 dpi), independent groups were subjected to behavioral tests, and brain tissues and sera were collected. Multiple behavioral and neurocognitive changes were detected in the early (30 dpi) and long-term (60 and 90 dpi) chronic infection. S+P therapy resolved locomotor alterations, anxiety, and depressive-like behavior, partially or transiently ameliorated hyperactivity and habituation memory loss. Analysis after therapy cessation showed that S+P therapy reduced the number of stimuli required for aversive memory consolidation. S+P therapy resulted in reduced brain cyst load, neuroinflammation and BBB disruption, and lowered systemic Th1-cytokine levels. Correlation analysis revealed association between IFNγ, TNF and MCP-1/CCL2 serum levels, brain cyst load and behavioral and neurocognitive alterations. Moreover, principal-component analysis (PCA-2D and 3D projections) highlighted distinction between clusters (noninfected; Veh-treated and S+P-treated infected). Thus, our data suggest that S+P therapy added gain to intrinsic brain cyst control and, direct or indirectly, ameliorated inflammation-related alterations, traits associated with behavioral and neurocognitive alterations.